Racial disparities in reported prenatal care advice from health care providers. - Kogan, M D (1994)
OBJECTIVES. The relationship between certain maternal behaviors and adverse pregnancy outcomes has been well documented. One method to alter these behaviors is through the advice of women's health care providers. Advice from providers may be particularly important in minority populations, who have higher rates of infant mortality and prematurity. This study examines racial disparities according to women's self-report of advice received from health care providers during pregnancy in four areas: tobacco use, alcohol consumption, drug use, and breast-feeding. METHODS. Health care providers' advice to 8310 White non-Hispanic and Black women was obtained from the National Maternal and Infant Health Survey. RESULTS. After controlling for sociodemographic, utilization, and medical factors, Black women were more likely to report not receiving advice from their prenatal care providers about smoking cessation and alcohol use. The difference between Blacks and Whites also approached significance for breast-feeding. No overall difference was noted in advice regarding cessation of drug use, although there was a significant interaction between race and marital status. CONCLUSIONS. These data suggest that Black women may be at greater risk for not receiving information that could reduce their chances of having an adverse pregnancy outcome.